Politeness Strategies in Giving and Responding to Compliments by All Characters in The Movies Entitled “Fundamentals of Caring” and “Wonder" - Fristando, Clara Adelia (Jurnal Bahasa, Sastra, dan Studi Amerika, 2022)
This study aims at finding the politeness strategies, the topics of compliment, and the compliment responses applied by all characters in two movies entitled The Fundamentals of Caring   and   Wonder.   The   data   were   taken   from   conversations   between   characters   in Fundamentals of Caring and Wonder which contain compliment and its response. This study employs Brown and Levinson’s politeness strategies in analyzing compliment and its response. This study also employs Wolfson’s Topics of Compliments to analyze the topics of compliment and Herbert’s theory of compliment responses (CR) to analyze the character’s compliment responses. The result shows that the characters in Fundamentals of Caring employ do not do the FTA, positive politeness strategy, and bald on record in giving and responding the compliments, while in Wonder the characters employ do not do the FTA, bald on record, positive politeness, and negative politeness strategy. In both movies, the topics of compliment employed by all the characters consist of topic of personal appearance, topic of general ability and topic of specific- act ability. In responding the compliments, the characters in Fundamentals of Caring apply Appreciation Token; Praise Upgrade; and Comment History, Scale down, Disagreement, and No acknowledgement. Meanwhile, the characters in Wonder apply Appreciation Token, Comment Acceptance, Comment History, Return, Scale Down, Question, Disagreement, and No Acknowledgement.